2014
DOI: 10.1521/psyc.2014.77.4.360
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence of and Risk Factors for Suicidal Ideation and Suicide Attempts in a Korean Community Sample

Abstract: Lifetime suicidal behavior was highly prevalent in Jeollabuk-do Province. The most significant risk factors were found to be social support, family disharmony, anger, depression, and low self-esteem in Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
1
18
1
2
Order By: Relevance
“…This finding is compatible with that of a study which found that low self-esteem was associated with suicidal intent, independently of the severity of depression [42]. A study recruiting 2964 community members also found that low self-esteem is one of the major risk factors related to SI [43], and another study revealed that low self-esteem and low sense of self-efficacy may lead to a suicide attempt [44]. Two other studies in elderly inpatients [1, 5] revealed that factors related to SI were use of antidepressants, previous deliberate self-harm, pessimism, length of hospital stay, history of traumatic events, the level of social support, and the presence of depression, which was found to be a major determinant of SI in many studies [6, 1014].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is compatible with that of a study which found that low self-esteem was associated with suicidal intent, independently of the severity of depression [42]. A study recruiting 2964 community members also found that low self-esteem is one of the major risk factors related to SI [43], and another study revealed that low self-esteem and low sense of self-efficacy may lead to a suicide attempt [44]. Two other studies in elderly inpatients [1, 5] revealed that factors related to SI were use of antidepressants, previous deliberate self-harm, pessimism, length of hospital stay, history of traumatic events, the level of social support, and the presence of depression, which was found to be a major determinant of SI in many studies [6, 1014].…”
Section: Discussionsupporting
confidence: 89%
“…Suicide attempts have been reported to occur 10–20 times more frequently than completed suicides [ 3 ]. Different studies have shown that the lifetime prevalence in different countries varies widely, ranging from 1.3 to 6.2 % [ 4 , 5 ]. Among various suicide methods, deliberate self-poisoning (DSP) is typically classified as a low-lethality method [ 6 , 7 ], but the majority of self-harm episodes involve poisoning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate depression, the Korean version of the Zung Depression Scale, a 20‐item self‐report questionnaire that measures an individual's present level of depressive thoughts and behaviours, was used . Each item is rated on a Likert‐type scale coded from 1 (a little of the time) to 4 (most of the time), with higher scores indicating higher levels of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Self‐esteem was measured by the Rosenberg Self‐Esteem Scale, which consists of 10 items related to self‐esteem . Each item was rated on a Likert‐type scale, from 1 (strongly agree) to 4 (strongly disagree).…”
Section: Methodsmentioning
confidence: 99%